2002
DOI: 10.1152/japplphysiol.00049.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperthermia on cerebral blood flow and metabolism during prolonged exercise in humans

Abstract: The development of hyperthermia during prolonged exercise in humans is associated with various changes in the brain, but it is not known whether the cerebral metabolism or the global cerebral blood flow (gCBF) is affected. Eight endurance-trained subjects completed two exercise bouts on a cycle ergometer. The gCBF and cerebral metabolic rates of oxygen, glucose, and lactate were determined with the Kety-Schmidt technique after 15 min of exercise when core temperature was similar across trials, and at the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
200
4
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(219 citation statements)
references
References 40 publications
8
200
4
7
Order By: Relevance
“…Rasmussen et al (30) suggested that the observed increase in CO 2 reactivity, coupled with decreases in PET CO 2 , provides a mechanistic basis for previously observed reductions in cerebral blood flow when subjects exercised in the heat (25,26). The most obvious reason for conflicting findings with respect to cerebral vascular CO 2 reactivity between the present study and that of Rasmussen et al (30) is the absence of exercise in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Rasmussen et al (30) suggested that the observed increase in CO 2 reactivity, coupled with decreases in PET CO 2 , provides a mechanistic basis for previously observed reductions in cerebral blood flow when subjects exercised in the heat (25,26). The most obvious reason for conflicting findings with respect to cerebral vascular CO 2 reactivity between the present study and that of Rasmussen et al (30) is the absence of exercise in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Significantly different from * control and † rest (P Ͻ 0.05). (24,46), and the associated systemic dopamine response could be affected by sensory feedback arising secondary to the increased body temperature. Thus dopamine in the sympathetic ganglia is secreted mainly from the sensory neurons (3).…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were successfully rehydrated between trials, as indicated by similar hemoglobin concentrations at the onset of the trials (mean range between bouts: 135-137 g/l). Also, in these trained subjects, 1 h of rest is sufficient for the cerebral metabolism, the core and brain temperatures, blood lactate, and plasma osmolarity to recover from the first exercise bout, independent of whether or not hyperthermia is superimposed (46,49). In the present study, fatigue was considered as increased difficulty in retaining the required power output, and during exercise the subjects expressed their ratings of perceived exertion (RPE) on the Borg scale (9), allowing for an evaluation of their perception of effort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a reduction in cerebral blood flow, cerebral oxygen delivery does not appear to be jeopardized during exercise and thermally stressful conditions. 59 One apparent consequence of reduced cerebral blood flow was a reduction of total body heat removal as there was not temperature gradient between the brain and the rest of the body due to increased core temperature.…”
Section: Physiological Responses To Heat Stressmentioning
confidence: 99%